Revising, Correcting, and Transferring Genes. Issue 8 (2nd August 2020) - Cwik, Bryan
Abstract: The distinction between germline and somatic gene editing is fundamental to the ethics of human gene editing. Multiple conferences of scientists, ethicists, and policymakers, and multiple professional bodies, have called for moratoria on germline gene editing, and editing of human germline cells is considered to be an ethical "red line" that either never should be crossed, or should only be crossed with great caution and care. However, as research on germline gene editing has progressed, it has become clear that not all germline interventions are alike, and that these differences make a significant moral difference, when it comes to ethical questions about research, regulation, clinical application, and medical justification. In this paper, I argue that, rather than lumping all germline interventions together, we should distinguish between revising, correcting, and transferring genes, and I assess the consequences of this move for the ethics of gene editing.